Analisis Pengalaman Wajib Pajak Dalam Proses Penagihan PBB P2 Dan Strategi Peningkatan Kepatuhan - Suwandi, Suwandi; Dwi Artha Qairi, Rakhdinda (Jurnal Ilmiah Muqoddimah: Jurnal Ilmu Sosial, Politik dan Hummaniora, 2024)
The process of collecting urban and rural land and building tax (PBB P2) is an important aspect of the taxation system in Indonesia. However, taxpayers' experiences in this process can vary, thus affecting their level of tax compliance. Even though the PBB P2 tax plays an important role in regional income, some taxpayers have difficulty understanding the details of the tax owed and the payment procedures. This variation in experience triggers problems in tax compliance. In this context, the research aims to analyze taxpayers' experiences in the PBB P2 tax collection process and identify strategies to increase compliance. This research uses a qualitative approach with in-depth interviews with several taxpayers and content analysis of programs that have been implemented by the Lamandau Regency Regional Government. The results of the analysis show that there are variations in taxpayer experience in the PBB P2 tax collection process. Strategies to increase compliance include tax education, incentives, improving tax services, transparency in the use of tax funds, and active community participation. The Lamandau Regency Regional Government needs to strengthen tax education programs, optimize incentives, improve tax customer service, encourage transparency in the management of tax funds, and encourage active community participation to increase tax compliance.